PEMBANGUNAN APLIKASI SERVER WARI ENDA - Ertina Sabarita Barus; Christian Jorena Sitepu (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2016)
Application Server Wari Enda is a useful application to perform charging data- data, that the church's message GBKP (momo), devotional, devotional author profile, songbook GBKP, foster children, as well as information GBKP. In the preparation of this paper the author only do the charging data GBKP church bulletin (momo), devotional, and the author's profile afterthought. The author also build a simple web server that can make the process of inputting data into a database which has been built using the PHP programming language that in her also includes the encoding process in the form of JSON (Java Script Object Notation) so that the data entered is legible by Enda Wari Android application users.